Raul córdula: 30 anos de pintura - de olho no mundo a sublime re-construção do olhar - Ferreira, Eleine Freire Bourdette (1992)
This study which is both descriptive and explanatory aims at a critical view of the work of Raul Córdula, a fine artist born in Brazilian state of Paraíba. Specially marked by a combination of geometrical as well as gesture signs, Córdula's work has given shape to an unique world of figures and forms in the domain of fine arts. The methodology employed includes critical notes on the artistic trend named "Nova Objetividade", the formal abstraction prevailing in the fine arts of the 60's, besides transcripts of personal interviews with Raul Córdula conducted by the Authoress. By relating archaic signs, as those found in the inscriptions of Pedra do Ingá, to both geometrical and abstract ones, Córaula's technical devices and concious artistry confront the onlooker with an intriguing affinity between the ancient and the new. This Dissertation seeks to demonstrate the relevance of Córdula's artistic work, and also suggests that such work is a distinctive feature of fine arts in Brazil.